Cardiovascular toxicity profiles of immune checkpoint inhibitors with or without angiogenesis inhibitors: a real-world pharmacovigilance analysis based on the FAERS database from 2014 to 2022 - Wang, Yanfeng; Cui, Chanjuan; Deng, Lei; Wang, Lin; Ren, Xiayang (Frontiers in Immunology, 2023)
Background: Immune checkpoint inhibitor (ICI) combined with angiogenesis inhibitor (AGI) has been becoming increasingly available for multiple types of cancers, whereas the cardiovascular safety profiles of such combination therapy in real-world settings has not been elucidated to date. Therefore, we aimed to comprehensively investigate the cardiovascular toxicity profiles of ICI with AGI in comparison with ICI alone. Methods: The Food and Drug Administration Adverse Event Reporting System (FAERS) database from 1st quarter of 2014 to 1st quarter of 2022 was retrospectively queried to extract reports of cardiovascular adverse events (AEs) associated with ICI alone, AGI alone and combination therapy. To perform disproportionality analysis, reporting odds ratio (ROR) and information components (IC) were calculated with statistical shrinkage transformation formulas and lower limit of 95% confidence interval (CI) for ROR (ROR025) > 1 or IC (IC025) > 0 with at least 3 reports was considered statistically significant. Results: A total of 18 854 cardiovascular AE cases/26 059 reports for ICI alone, 47 168 cases/67 595 reports for AGI alone, and 3 978 cases/5 263 reports for combination therapy were extracted. Compared to the entire database without AGI or ICI, cardiovascular AEs were over-reported in patients with combination therapy (IC025/ROR025=0.559/1.478), showing stronger signal strength than those with ICI alone (IC025/ROR025=0.118/1.086) or AGI alone (IC025/ROR025=0.323/1.252). Importantly, compared with ICI alone, combination therapy showed a decrease in signal strength for noninfectious myocarditis/pericarditis (IC025/ROR025=1.142/2.216 vs. IC025/ROR025=0.673/1.614), while an increase in signal value for embolic and thrombotic events (IC025/ROR025=0.147/1.111 vs. IC025/ROR025=0.591/1.519). As for outcomes of cardiovascular AEs, frequency of death and life-threatening was lower for combination therapy than ICI alone in noninfectious myocarditis/pericarditis (37.7% vs. 49.2%) as well as in embolic and thrombotic events (29.9% vs. 39.6%). Analysis among indications of cancer showed similar findings. Conclusion: Overall, ICI combined with AGI showed greater risk of cardiovascular AEs than ICI alone, mainly due to increase in embolic and thrombotic events while decrease in noninfectious myocarditis/pericarditis. Moreover, compared with ICI alone, combination therapy presented lower frequency of death and life-threatening in noninfectious myocarditis/pericarditis and embolic and thrombotic events.